The Threat of Ambient Air Pollution in Kathmandu, Nepal. (10th July 2018) - Saud, Bhuvan; Paudel, Govinda
Abstract : Air pollution has been a major problem of 21st century for both developed and developing world. It has a negative impact on various environmental aspects which directly or indirectly affect the quality of human health. Nepal, especially Kathmandu, in the current situation, is observing rapid urbanization and various infrastructure development projects. As a result, these sorts of human activities have been responsible for increasing air pollution in an enormous rate inside Kathmandu Valley. Chronic exposure of deteriorated air increases the chance of Noncommunicable Disease (NCD) like lung disease, heart disease, and cancers. Short term exposures also invite respiratory diseases and allergy. This review is an attempt to summarize the updated knowledge on the threat of air pollution on public health and discuss the sources of air pollutants in Kathmandu. We reviewed the literatures that were published in PMC, MEDLINE, life science journals, and organization official websites and finally came up with the findings and their interpretation that reveal the current scenario in the context of Kathmandu's air quality status and its impact on human health. The knowledge about the invisible killer's role in causing acute and chronic diseases may help in finding out the answer of the question regarding its effect and prevention.